Climate change, inequality, and childhood stunting in African countries - Nabin Pradhan; Elizabeth Ludwig-Borycz; Arun Agrawal (Proceedings of the National Academy of Sciences, 2026)
Childhood stunting is associated with increased mortality, higher risk of chronic disease, impaired cognitive development, lower educational attainment, reduced economic opportunities, and intergenerational transmission of stunting. These risks are likely to intensify as climate change exacerbates key drivers of undernutrition, making it important to understand how rising temperatures affect stunting and the role of socioeconomic inequality in this relationship. We analyze data from 34 African countries from 2004 to 2020 using Demographic and Health Surveys (DHS), combining observed temperature variability from ERA5 reanalysis with anthropogenic temperature anomalies derived from Detection and Attribution Model Intercomparison Project (DAMIP) simulations. Using a mediation framework, we examine pathways linking temperature anomalies, inequality, and child stunting. Results based on observed temperature anomalies show no direct climate effect on stunting or inequality, but a positive and statistically significant association between inequality and stunting. In contrast, anthropogenic temperature anomalies are positively associated with inequality and stunting, with a 1 °C increase linked to a 3.45% rise in child stunting (SE = 1.52, P = 0.023), with no evidence of mediation through inequality. Notably, we find a consistent positive association between inequality and stunting across specifications. These findings suggest that reducing inequality, together with investments in education, sanitation, and household resilience, could substantially lower stunting rates and protect child health in a warming world.